PROSPECTS FOR THE DEVELOPMENT OF MULTIMODAL TECHNOLOGIES OF PASSENGER TRANSPORTATION AT THE REGIONAL LEVEL IN THE ASPECT OF “GREEN” LOGISTICS - Boiko, S. M.; Kotov, O. B. (Systems and Technologies, 2023)
The article emphasizes that an important factor in the development of the world economy is the level of the provision of transport services, which encourages the development of transport infrastructure and the constant improvement of the efficiency and optimality of its functioning. The dynamics of passenger transportation in Ukraine is presented in retrospect, which showed a significant decrease. It is also determined that the specific weight of the types of transport in the context of passenger transportation has undergone changes over the past 30 years. Directions and approaches to the implementation of elements of “green” logistics are given. Combinations of types of transport are proposed for introduction into the structure of passenger transportation at the regional level in Ukraine in the aspect of “green” logistics, namely the combination of road ground electric transport and domestic aviation, road ground electric transport and river transport. Prospective combinations of types of transport are proposed for introduction into the structure of passenger transportation at the regional level in Ukraine in the aspect of “green” logistics, namely the combination of railway transport and hydrogen fuel and ground electric transport, river transport and hydrogen fuel and ground electric transport, domestic aviation and hydrogen fuel and ground electric transport In the study, the prerequisites for the development of multimodal technologies of passenger transportation at the regional level on the territory of Ukraine in the aspect of “green” logistics are determined. In order to introduce multimodal passenger transport technologies at the regional level, a number of transformations must first be carried out. First of all, it is necessary to determine the capabilities of the relevant region, where the implementation of multimodal technologies is planned, in terms of resource provision. Secondly, it is necessary to decide on promising and current passenger routes. Thirdly, the development of the appropriate transport infrastructure should be ensured.